PERANCANGAN SISTEM INFORMASI REKAM MEDIS RAWAT JALAN PADA RUMAH SAKIT MAYAPADA TANGERANG MENGGUNAKAN METODE PROTOTYPE BERBASIS WEB - Tangkas Prassetio; Nur Rofiq (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Mayapada Hospital is one of the best private hospitals that requires an information system that is accurate, reliable, and sufficient to improve its services to patients.So far, the recording and processing of existing medical record data is still using a simple system. Simple data management, has many drawbacks besides taking a long time, its accuracy is also not acceptable. This can reduce the quality and quality of the services provided by the clinic. Meanwhile, with the activities of patients and doctors who are quite a lot, it has caused various problems from daily services, especially in handling patient medical record data. For this reason, applying the Medical Record Application Using the WEBBased Prototype Method which is expected to provide convenience in managing patient medical record data to support improving health services to patients. And in the application of medical record applications, the benefits can be felt by many parties, both in terms of users (admins), doctors, and patients.